A Review on Advanced FeNi-Based Catalysts for Water Splitting Reaction - Li, Dongze; Liu, Hui; Feng, Ligang (Energy & fuels, 2020)
Water splitting as an advanced energy conversion technology driven by sustainable energy is attracting ever-increasing attention for clean hydrogen fuel generation from water. Two fundamental reactions, hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), are involved, and cost-effective catalysts are required to fulfill the energy transfer process. Non-precious-metal catalysts have been proposed as the mainstay for future commercial applications. Among them, iron–nickel (FeNi)-based catalysts are very promising benefiting from the FeNi synergistic interaction in promoting the basic reactions. With the help of rational structure design, composition optimization, and electronic state tuning, advanced catalysts based on FeNi have been extensively reported. Herein, we focus on the varied FeNi-based catalysts for water splitting reactions. Before reviewing the literature, some descriptors and perspective comments are first given in the parameter evaluation part that might be helpful for understating the catalytic capability. In light of the extensive reports, some typical examples of FeNi-based catalysts classified into FeNi-alloy, phosphides, oxides, layered double hydroxides, sulfides, tellurides, selenides, and fluorides are introduced in detail. Combined with these advanced catalysts and the performance evaluation, this review will be helpful for readers in understanding the advanced progress on FeNi-based catalysts for water splitting reaction. Problems and challenges are also discussed demonstrating that efficient catalysts that can maintain high activity and stability are still highly desired. A brief perspective on FeNi-based catalysts is proposed that we hope can be a good complement to the existing literature for a better understanding of FeNi-based catalysts for water splitting reaction.